Technology Acceptance Model and Government Support to Use of Islamic Fintech for MSMEs in Metro City - Swandini, Witantri Dwi; Ulva Anggara, Ose Atika (Jurnal Internasional Ekonomi Islam, 2023)
The purpose of this research is to find out how to accept Islamic fintech based on influencing factors. These factors are divided into internal and external factors. Internal factors consist of technology readiness, while external factors include government support in the acceptance of Islamic fintech in Micro, Small and Medium Enterprises (MSMEs) in Metro City. The respondents of this research are MSMEs in Metro City who have adopted fintech on their business activities. The data analysis method used in this research is a quantitative method using the Structural Equation Model (SEM). The type of data used is primary data obtained by distributing questionnaires assisted by the results of interviews with respondents. By using the Technology Acceptance Model, this research tries to analyze the model of factors that influence the application of fintech used by MSMEs in Metro City. The research results show that the external factors tested in this research can influence behavioral intentions through perceived benefits, perceived ease of use in implementing fintech in business activities carried out by MSMEs. Apart from these factors, there are also other factors such as government support provided in the form of training/capital assistance and expert assistance. Limitations in this research are the limitations of the research location and research variables used. This is caused by limited funds and time for collecting data in the field. Contributions of this research are expected to help MSMEs to maximize the application of fintech in business activities, as a consideration for local governments to provide more training and assistance for MSMEs in using fintech.